Using Project- Based Learning to Improve Students’ Speaking Abilities of Madrasa Students - Badrut Tamam, Mas Muhammad (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
Speaking is one of the language skills learned in English language learning as a compulsory subject. This skill is productive because it allows students to use the target language actively for real communication, so it is an aspect that must receive attention in teaching English as a foreign language. One of the techniques that can be used to improve students' speaking ability is Project-Based Learning (PjBL). This study aims to test whether the use of PjBL can improve students' speaking skills, especially in the aspects of pronunciation and vocabulary. This study used a pre-experiment design with a One Group Pretest-Posttest model, involving 40 madrasa students. Data was obtained through pretest and posttest. The pretest results showed that the average score of students was 34.47, while the posttest showed that the average score increased to 74.82. The results of statistical analysis showed significant differences with the observed “t” value (to = 23.25) greater than the “t” table value (tt 5% = 2.02 and tt 1% = 2.71). Thus, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted. This finding proves that the application of Project-Based Learning significantly improves students' speaking ability. In addition, this method creates more fun and effective learning, so students can learn without feeling burdened.